On drifting rules and standards - Ortmann, Günther (Scandinavian journal of management, 2010)
Rules and standards are considered to be of vital importance for the functioning not only of organizations but of societies as well. The difficulties and paradoxes associated with the concept of rules and rule-following are analyzed much more frequently in the context of philosophy than of social science. In this paper, I will draw on the writings of Wittgenstein and Derrida to examine four particular characteristics of rules and standards: first, the dependence of their validity and meaning on the practice of rule-following. Second, properties that have led me to describe them as pharmaka in Derrida's (1997) sense, which means medicine or poison and possibly illicit drugs. Third, their dependence on the possibility of rule-breaking, and fourth, their being inevitably subject to drift, which is beneficial in many cases but dangerous in others. I will argue that the drift of rules and standards becomes increasingly dangerous when more processes become path dependent. This paper examines four cases as examples of dangerous drifts in the context of organizations: the drift of environmental standards, the Challenger disaster, a friendly fire case in northern Iraq, and Michael Power's “audit explosion.”